SARS-CoV-2 vaccines induce a diverse spike-specific CD4+ T cell receptor repertoire in people living with HIV with low CD4 nadirs - Mercado, Alicia; Sop, Joel; Amanat, Steven; Zhang, Li; Chida, Natasha M.; Basseth, Christie R.; Gebo, Kelly A.; Antar, Annukka A. R.; Smith, Kellie N.; Zeng, Zhen; Blankson, Joel N. (Frontiers in Immunology, 2025)
People living with HIV with low CD4 T cell nadirs on antiretroviral therapy have suboptimal responses to immunization. We analyzed the SARS-CoV-2 spike-specific CD4+ T cell repertoire in individuals with CD4 nadirs of less than 100 cells/ul who received a primary SARS-CoV-2 mRNA vaccine series as well as the bivalent ancestral/BA.5 spike mRNA vaccine. We tested the hypothesis that antigenic imprinting would result in the preferential expansion of pre-existing cross-reactive T cells that were primed against the 4 common cold coronaviruses. We found that these individuals made robust effector and memory T cell responses to the SARS-CoV-2 spike protein that exceeded the responses to spike proteins from the common cold coronaviruses. Furthermore, in 4 individuals, the number of SARS-CoV-2 specific TCRs far exceeded the number of common cold coronavirus-specific T cell receptors. TCRs that were cross-reactive for common cold coronaviruses and SARS-CoV-2 comprised less than 10% of the total detected SARS-CoV-2 specific T cells. The diversity of the SARS-CoV-2 spike-specific repertoire in 6 study participants was comparable to that of the repertoire in vaccinated HIV healthy donors. Our data suggests people living with HIV with low CD4 nadirs can have significant functional immune reconstitution with little evidence of antigenic imprinting due to pre-existing T cell responses to common cold coronaviruses.